Handbook of research on strategic communication, leadership, and conflict management in modern organizations - Normore, Anthony H.; Javidi, Mitch, 1958-; Long, Larry W. (Advances in human resources management and organizational development (AHRMOD) book series., 2019)
"This book explores the theoretical and practical aspects of managing and solving conflicts and introduces updated approaches for refining communication and leadership skills. Featuring coverage on a broad range of topics such as emotional intelligence, organizational crises, and virtual team management"--